Kesulitan Mahasiswa Dalam Menganalisis Wacana Lisan (Spoken Discourse) Pada Kajian Discourse and Conversation - Ibrahim, Linda Fitri (IAIN Takengon, 2021)
Discourse Analysis examines the nature of language and the use of language in communication and also research and analyzes language use naturally, both spoken and written. The form of discourse is divided into two; namely spoken discourse and written discourse. There are several types of studies in discourse analysis which aim to analyze both spoken and written language and one of them is discourse and conversation. The scope of this research discussed about students’ understanding in analyzing spoken discourse in discourse and conversation. The research method used descriptive qualitative research. The source of data was the sixth semester students at English department IAIN Takengon. The number of sample was 18 students of English department. The techniques of data collection were observation, interview and documentation. Based on the result of research, it can be concluded that the sixth semester students of English department IAIN Takengon still have difficulties in analyzing discourse and conversation. From the result of research, it can be seen that the total sum of error in discourse and conversation about transcription convention was 13 errors, for sequence and structure in conversation was 25 errors, for preference organization was 8 errors, for feedback was 8 errors and 4 errors for repair.